Energy harvesting wireless optical microsystems - Haydaroğlu, İskender. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
This thesis covers a novel approach to photovoltaic energy harvesting and optical data transmission in the context of millimeter-scaled smart autonomous microsystems through the use of a single light emitting diode (LED) to both e ciently harvest optical energy and transmit data to enable wireless, batteryless operation. A proof of concept design for demonstrating the viability of the use of a LED in the proposed manner, harvesting optical energy and transmitting a xed device ID optically through the same LED using a transmitter based on a continually running charge pump is presented. Next, a low voltage temperature sensor design is integrated into the existing design, to prove by example that the harvested voltage from the LED is high enough that it requires no voltage boosting to power essential analog blocks such as sub-bandgap references, oscillators, and comparators, as opposed to integrated CMOS photovoltaic harvesting. Finally, an alternative, energy e cient optical transmitter architecture and a new ultra low power, ultra low energy temperature sensor are designed and integrated into a single chip. The scalable, inverter based switched capacitor boosting transmitter uses the trickle current from the LED to charge its capacitors directly with minimized losses in e ciency, transmitting data with 1 nJ/bit to a receiver designed and built in-house for up to 10 cm distance. The temperature sensor consumes less than 3 W, features digital o set correction and an adaptive full-partial conversion algorithm to minimize the conversion time, e ectively reducing energy per conversion from 0.6 nJ-3 nJ to 0.15 nJ-0.75 nJ. Total power consumption is in the order of 6 W, harvested by a 0.1 mm2 LED, making the system viable for millimeter-scaled outdoor solar harvesting applications. All three designs were fabricated in UMC 0.18 m CMOS process and tested in-house.
Keywords: Wireless power transmission.; Metal oxide semiconductors, Complementary